Optimal use of tranexamic acid for total hip arthroplasty: A network meta-analysis. - Byung-Ho Yoon; Tae-Young Kim; Young Seung Ko; Young-Kyun Lee; Yong-Chan Ha; Kyung-Hoi Koo (PLoS ONE)
Background Tranexamic acid (TXA) has been demonstrated to minimize blood loss after total hip arthroplasty. There are three main routes: intravenous (IV), intra-articular (topical), and combined (IV and topical) but little consensus support which is most effective and safe. We performed network meta-analysis.to assess the comparative efficacy and safety of three different administration routes of TXA. Methods Twenty-five randomized controlled trials (RCT) were evaluated. Interventions were classified as: combined, IV multiple, IV single, topical and placebo. The primary outcome was effectiveness (transfusion rate, total blood loss, and total drain out). The secondary outcome was safety, based on the incidence of deep venous thrombosis (DVT) and pulmonary embolism (PE). Results A total of 2227 patients were included in the 5 categories: 564 IV single, 319 IV multiple, 398 topical, 120 combined, and 826 placebo. A network meta-analysis identified the most effective interventions in terms of reducing the need for transfusion as follows: combined = 98.2%, IV single = 54.0%, IV multiple = 78.6%, topical = 66.1%, placebo = 0.0%. Compared with placebo, the IV single, IV multiple, topical, and combined interventions showed no difference in the rate of occurrence of DVT and PE. Conclusions A network meta-analysis indicated that combined administration of TXA (IV and topical) was effective in reducing the transfusion rate after hip arthroplasty compared with IV or topical alone. As no high-risk patients were evaluated in the RCTs, it is not known whether the combined method is safer for patients susceptible to DVT or PE.